2018
DOI: 10.1021/acs.est.8b02988
|View full text |Cite
|
Sign up to set email alerts
|

Do Sanitation Improvements Reduce Fecal Contamination of Water, Hands, Food, Soil, and Flies? Evidence from a Cluster-Randomized Controlled Trial in Rural Bangladesh

Abstract: Sanitation improvements have had limited effectiveness in reducing the spread of fecal pathogens into the environment. We conducted environmental measurements within a randomized controlled trial in Bangladesh that implemented individual and combined water treatment, sanitation, handwashing (WSH) and nutrition interventions (WASH Benefits, NCT01590095). Following approximately 4 months of intervention, we enrolled households in the trial’s control, sanitation and combined WSH arms to assess whether sanitation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
78
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 65 publications
(88 citation statements)
references
References 57 publications
7
78
3
Order By: Relevance
“…Our findings of no difference in the prevalence or abundance of T. trichiura in soil between the sanitation and control arms supports the possibility that the observed reduction in T. trichiura infection in the sanitation arm could be a chance finding. Our findings are also consistent with other environmental measurements conducted among trial households showing no reduction in E. coli contamination or bacterial, viral and protozoan pathogens in soil (or other types of environmental samples) between the sanitation and control arms (48,49). A parallel study nested within the WASH Benefits Kenya trial also found no reduction in STH eggs in soil from the sanitation intervention (18).…”
Section: Discussionsupporting
confidence: 91%
“…Our findings of no difference in the prevalence or abundance of T. trichiura in soil between the sanitation and control arms supports the possibility that the observed reduction in T. trichiura infection in the sanitation arm could be a chance finding. Our findings are also consistent with other environmental measurements conducted among trial households showing no reduction in E. coli contamination or bacterial, viral and protozoan pathogens in soil (or other types of environmental samples) between the sanitation and control arms (48,49). A parallel study nested within the WASH Benefits Kenya trial also found no reduction in STH eggs in soil from the sanitation intervention (18).…”
Section: Discussionsupporting
confidence: 91%
“…Findings from our trials provide an urgent call for research to identify interventions that radically reduce faecal contamination in the household environment of low-income and middle-income countries. We term this transformative WASH. Transformative WASH might require high community coverage of improved sanitation facilities, 58 complete separation of animal faeces from people's living environments, 12,49 continuous and convenient access to uncontaminated water, 59 reductions in faecal contamination on surfaces where young children crawl and play, 46 new technologies to deliver WASH services which might differ from those implemented in high-income countries, 60 or different modalities of behaviour change. 61 Regardless of chosen technologies and interventions, transformative WASH will certainly require strengthened support for governance systems of financing, operations, monitoring, evaluation, and regulation.…”
Section: Resultsmentioning
confidence: 99%
“…In the WASH Benefits Bangladesh trial, the combined WASH and water chlorination interventions reduced the prevalence of Escherichia coli in stored drinking water and in food, but about 50% of the stored drinking water and 40% of the food still had detectable E coli, and none of the WASH interventions reduced E coli on the caregivers' or children's hands, ambient water, courtyard soil, or sentinel toys. 46,47 The combined WASH and handwashing interventions significantly reduced Giardia infection by 25%; however, 26-30% of children who received those WASH interventions were still infected with Giardia. 35 The combined WASH and water chlorination interventions reduced hookworm infection by 29-33%, but about 6% of children who received those WASH interventions were still infected with hookworm.…”
Section: Table: Effect Of Intervention On Diarrhoea For Randomised Comentioning
confidence: 99%
“…We also sampled a random subset of households in the single water and handwashing arms to assess the impact of combined vs individual interventions. The sanitation arm was not sampled as a previous assessment showed no early environmental impact in this arm 23 and a separate longitudinal study is underway to assess the long-term effect of sanitation on environmental contamination (manuscript forthcoming). Sampling was conducted at two time points, approximately 1 and 2 years after intervention initiation, to match the timing of the trial’s health outcome measurements (see Supporting Information (SI) Text S1 and Figure S1 for details of all environmental assessments nested within WASH Benefits).…”
Section: Methodsmentioning
confidence: 99%